(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Ricin, a highly toxic protein found in castor bean seeds, is a potential agent for biological warfare and a major concern for national authorities worldwide. The assassination of Georgi Markov using ricin highlighted the forensic importance of detecting this poison. The present study aims to develop an analytical method, to facilitate detection and forensic analysis of ricin. The study employs visual characterization to examine the physical features of the seeds, and thin-layer chromatography (TLC), and UV visible spectrometry for chemical examination to confirm the presence of ricin. The research design involves conducting solvent extraction and TLC, followed by optical characterization by the use of UV-Vis spectrometry, for quick and unambiguous identification of ricin for forensic purposes. This study reports, for the first time, extensive morphological analysis of castor seeds, green solvent extraction and optimization of TLC. By developing an easy and effective method for the examination of castor seeds and ricin, this study provides a reliable additional test for detecting ricin in castor seeds, which is crucial for forensic and security purposes.